Astragalus montis-hashtadi (Fabaceae), a new species of A. sect. Microphysa from the Central Zagros, Iran, based on morphological and molecular evidence - Roofigar, Azadeh Akhavan; Maassoumi, Ali Asghar; Rad, Mohammad Amini (Phytotaxa, 2026)
A new species of Astragalus sect. Microphysa, A. montis-hashtadi Akhavan & Maassoumi, is described and illustrated from Hashtad Mountain in the Central Zagros range, western Isfahan Province, Iran. The species is characterized by its compact cushion habit, densely silvery tomentose indumentum completely covering the leaf surface, very short peduncles, and small, globose racemes. Morphological comparisons with closely related taxa (A. microphysa, A. microphysopsis, and A. reuterianus) confirm its distinctness, supported by consistent diagnostic differences in indumentum texture and calyx morphology. Phylogenetic analysis based on combined nuclear ITS and plastid rpl32-trnL sequences places A. montis-hashtadi within A. sect. Microphysa, forming a subclade close to A. microphysa. The species is narrowly endemic to calcareous rocky slopes at elevations around 3000 m a.s.l., where it occurs in alpine habitats. Because of its extremely limited range, small population size, and habitat disturbance from grazing and mining, it is assessed as Critically Endangered (CR) under the IUCN criteria. This discovery highlights the Central Zagros as an important center of micro-endemism and diversification within the spiny taxa of Astragalus.